Inside interesting integrals : a collection of sneaky tricks, sly substitutions, and numerous other stupendously clever, awesomely wicked, and devilishly seductive maneuvers for computing hundreds of perplexing definite integrals from physics, engineering, and mathematics (plus numerous challenge problems with complete, detailed solutions) /: a collection of sneaky tricks, sly substitutions, and numerous other stupendously clever, awesomely wicked, and devilishly seductive maneuvers for computing hundreds of perplexing definite integrals from physics, engineering, and mathematics (plus numerous challenge problems with complete, detailed solutions). ([2020]) - Nahin, Paul J
No abstract available